2014
DOI: 10.4028/www.scientific.net/amr.1063.42
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Development and Mechanical Properties of a Hot Stamped Low-Carbon Advanced High Strength Steel Treated by a Novel Dynamic Carbon Partitioning Process

Abstract: To make steel exhibit attractive properties as high strength and good ductility, this paper presents a novel one step method for forming-Q&P integration—Hot Stamping-Dynamic Partitioning (HS-DP) process. The proposed HS-DP process is simulated with salt bath heat treatment. The effect of microstructure and mechanical properties in a low-carbon AHSS with different cooling rate of the new process is investigated by using scanning electron microscopy (SEM), X-ray diffraction (XRD) and tensile test methods. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The chemical composition of the HP-DP steel studied in this work is Fe-0.19C-1.55Si-1.53Mn-0.95Ni-1.01Cr-0.45Mo-1.01Cu-0.033Ti-0.0027B-0.025Al (wt-%) as reported in [7,9,10]. The steel was melted in a vacuum furnace, hot forged to a slab of 60 mm thickness and hot rolled to the blank of 4 mm thickness.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The chemical composition of the HP-DP steel studied in this work is Fe-0.19C-1.55Si-1.53Mn-0.95Ni-1.01Cr-0.45Mo-1.01Cu-0.033Ti-0.0027B-0.025Al (wt-%) as reported in [7,9,10]. The steel was melted in a vacuum furnace, hot forged to a slab of 60 mm thickness and hot rolled to the blank of 4 mm thickness.…”
Section: Methodsmentioning
confidence: 91%
“…Following this, the authors of this paper proposed the integrated hot pressing and dynamic partition (HP-DP) process [9,10]. The feasibility of the process was proved by physical simulations and high PSE level up to 25,600 MPa% with a tensile strength of 1600 MPa and an elongation of 16% could be achieved in the developed low-carbon press-hardened steels.…”
Section: Introductionmentioning
confidence: 99%
“…Then the authors proposed the HP-DP process [15], for which the temperature-time profile can be shown in Fig. 1. …”
Section: Design Concept Of Hf-dp Processmentioning
confidence: 99%